High-resolution integrated calcareous plankton biostratigraphy and magnetostratigraphy at the Oligocene-Miocene transition in Southwestern Atlantic Ocean - GENNARI, Rocco; PERSICO, Davide; TURCO, Elena; VILLA, Giuliana; IACCARINO, Silvia Maria; Florindo, Fabio; Lurcock, Pontus C.; de Santana dos Anjos Zerfass, Geise (Geological Journal, 2018)
After the formalization of the base of the Miocene in the Lemme‐Carrosio section (Italy) at thebase of Subchron C6Cn.2n, the calcareous plankton biostratigraphy was refined in several openocean Deep Sea Drilling Project/Ocean Drilling Program sites. However, high‐resolution quanti-tative biostratigraphic studies, integrating planktonic foraminifera and calcareous nannofossils,are still lacking for the time interval spanning the Oligocene–Miocene transition. Here, we pres-ent a reinvestigation of Deep Sea Drilling Project Hole 516F (Rio Grande Rise) and 4 oil wellsdrilled by Petróbras Brasileiro SA in the Campos Basin (SW Atlantic Ocean). We identified 12planktonic foraminiferal and 18 calcareous nannofossil bioevents that have been integrated withan updated magnetostratigraphy of Hole 516F allowing the correlation with the GPTS and theidentification of the Oligocene/Miocene boundary (base of Subchron C6Cn.2n) between theTop ofSphenolithus delphixand the Base of commonParagloborotalia kugleri. Furthermore, ourresults give new insights on the reliability of major calcareous plankton events across theOligocene–Miocene transition: (a) theSphenolithus ciperoensisTop, theS. delphixBase and Top,and theSphenolithus cometaBase are reliable events at a global scale; (b) the Bases ofGloboquadrina dehiscensandSphenolithus disbelemnos>4μm are correlatable events only withinthe study sector of the SW Atlantic Ocean; and (c) theGloboturborotalita ciperoensisTop,Globoturborotalita angulisuturalisTop, andSphenolithus procerusBase are diachronous. Finally,previously unreported biostratigraphic data, such as the distribution range ofS. disbelemnos<4μmandSphenolithuscf.S. pseudoheteromorphus, theTenuitellinata praestainforthiacme interval, andthe Top of commonGlobigerinoides primordiuswere identified in the Campos Basin.